Peningkatan VO2maks Pasca Latihan Tabata Selama Masa New Normal COVID-19 Pada Siswa SMA Overweight - Septyaningrum Putri Purwoto (SATRIA : Journal of Sports Athleticism in Teaching and Recreation on Interdisciplinary Analysis, 2022)
This study aims to determine the effect of Tabata training during the new normal period of COVID-19 on overweight high school students. This research includes the type of experimental research. The sample in this study were male students at Wachid Hasyim Sidoarjo High School who were overweight and male. Tabata exercises are performed 15 times with a frequency of 3x a week. Data analysis in this study used the MannWhitney test. The results showed that the p value (0.000) < 0.005 indicated that there was a significant difference in effect. The conclusion obtained in this study was that Tabata exercise in overweight students during the new normal period of COVID-19 experienced a significant increase.